The Reading Competency Test for Indonesian History-Major Students - Dinar Martia Azizah (ITScience (Information Technology and Science), 2026)
The development of English language skills among students in the History Education program predominantly focuses on reading. To assess their reading ability, a reading competency test is administered, requiring students to respond to and construct answers. The objective of this study is to describe the various types of reading competency tests for Indonesian students majoring in history. Research is descriptive and qualitative. The study was conducted at a teacher-training and educational sciences institute that offers a History Education program. Data were collected through analysis of documents related to English-language learning assessments administered to first-semester students. The data analysis employed an interactive model comprising data condensation, data presentation, and drawing conclusions and verifying them. The results of the study indicate that reading competency tests requiring a response can be administered through multiple-choice questions. Based on the provided text, students are asked to determine which statements align with the text and which do not by selecting one of the provided answer choices. In tests that require constructing answers, students are given open-ended questions to stimulate critical thinking.Additionally, students are asked to paraphrase a text and summarize chapters from books. All test materials are sourced from world and Indonesian history textbooks, research articles, brochures of historical sites, and annual agendas from the Department of Culture and Tourism, all written in English. The assessment criteria for the reading competency test requiring constructed responses include content completeness (information), vocabulary, grammar, cohesion, coherence in paragraph construction, and, if the test is conducted orally, pronunciation and fluency. Selecting English test materials that align with students' academic disciplines is one implementation of the ESP (English for Specific Purposes) concept. Although the tests primarily assess students' reading comprehension, this does not mean other skills are neglected.